2015
DOI: 10.1097/cji.0000000000000083
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale Isolation of Highly Pure “Untouched” Regulatory T Cells in a GMP Environment for Adoptive Cell Therapy

Abstract: Adoptive cell therapy is an emerging treatment strategy for a number of serious diseases. Regulatory T (Treg) cells represent 1 cell type of particular interest for therapy of inflammatory conditions, as they are responsible for controlling unwanted immune responses. Initial clinical trials of adoptive transfer of Treg cells in patients with graft-versus-host disease were shown to be safe. However, obtaining sufficient numbers of highly pure and functional Treg cells with minimal contamination remains a challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…Moreover, ex vivo expansion also allowed us to obtain a purer product than that obtained by direct isolation. In our experience, largescale T reg cell selection using the CliniMACS isolation system from leukapheresis yielded a CD4 + CD25 + T-cell purity of 55% (range 42.6-62%), the majority of which expressed FoxP3, in keeping with the reported data from healthy subjects [40,46,47].In response to recent studies showing the negative effect of cryopreservation on T reg cell function [41,42], we have previously demonstrated that expanded T reg cells after thawing can effectively prevent the onset of xenogeneic GvHD as well as improve acute GvHD and survival in a mouse model of GvHD using immunosuppressed mice (i.e., NOD-SCID-gamma knockout mice) [7]. Herein, the in vitro data reported also confirmed our previous results for T reg cell expansion according to our GMP-compliant process from patients with end-stage LD or KD.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, ex vivo expansion also allowed us to obtain a purer product than that obtained by direct isolation. In our experience, largescale T reg cell selection using the CliniMACS isolation system from leukapheresis yielded a CD4 + CD25 + T-cell purity of 55% (range 42.6-62%), the majority of which expressed FoxP3, in keeping with the reported data from healthy subjects [40,46,47].In response to recent studies showing the negative effect of cryopreservation on T reg cell function [41,42], we have previously demonstrated that expanded T reg cells after thawing can effectively prevent the onset of xenogeneic GvHD as well as improve acute GvHD and survival in a mouse model of GvHD using immunosuppressed mice (i.e., NOD-SCID-gamma knockout mice) [7]. Herein, the in vitro data reported also confirmed our previous results for T reg cell expansion according to our GMP-compliant process from patients with end-stage LD or KD.…”
Section: Discussionsupporting
confidence: 83%
“…Although magnetic bead sorting for CD4 + /CD25 hi cells may incorporate CD127 lo , purity may remain inadequate because activated naive and especially memory Tcons express CD25 and are therefore difficult to separate by MACS from CD25 hi Treg population. Including more surface markers (e.g., CD45RA + , CD49d − , and CD39 hi ), can result in a better defined and purer Treg population; however, when using MACS, there is a limit to the number of markers that can be included [ 199 , 200 , 201 , 202 ].…”
Section: Translational Challengesmentioning
confidence: 99%
“…The infusion of either freshly isolated or ex vivo expanded Tregs can improve survival of recipients in acute GVHD, but it is generally believed that very large numbers of Treg cells are required to achieve therapeutic effects . Due to the relatively low frequency of nTregs in circulation (1–2% of total CD4 + T cell population in humans ) the purification of sufficiently large numbers of Tregs has been challenging or might not even be feasible in clinical practice without in vitro expansion . We established a protocol enabling the purification of Tregs and the subsequent liberation from isolation reagents in an one‐step enrichment process.…”
Section: Discussionmentioning
confidence: 99%